Host Innate Immune Responses to Acinetobacter baumannii Infection - Chen, Wangxue (Frontiers in Cellular and Infection Microbiology, 2020)
Acinetobacter baumannii has emerged as a major threat to global public health and is one of the key human pathogens in healthcare (nosocomial and community-acquired)-associated infections. Moreover, A. baumannii rapidly develops resistance to multiple antibiotics and is now regarded as a serious multidrug resistant pathogen globally. There is an urgent need to develop novel vaccines and immunotherapeutics as alternatives to antibiotics for clinical management of A. baumannii infection. However, our knowledge of host immune responses to A. baumannii infection and the identification of novel therapeutic targets are significantly lagging behind. This review highlights the recent advances and critical gaps in our understanding how A. baumannii interacts with the host innate pattern-recognition receptors, and induces a cascade of inflammatory cytokine and chemokine responses and the recruitment of innate immune effectors (such as neutrophils and macrophages) to the site of infection for effective control of the infection. Such knowledge will facilitate the identification of new targets for the design and development of effective therapeutics and vaccines to fight this emerging threat.